The Effect of Electronic Word of Mouth on Consumer Loyalty through Brand Trust in E-Commerce - Heriyana Heriyana; Abdi Fadhlan; shinta rahmani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of electronic word of mouth on consumer loyalty, both directly and indirectly through brand trust among Shopee users purchasing local MSME products. The study employed a quantitative approach with an explanatory and cross-sectional research design. Data were collected using a five-point Likert-scale questionnaire from 150 respondents selected through purposive sampling and analyzed using PLS-SEM with SmartPLS 4. The results demonstrate that electronic word of mouth has a positive and significant effect on consumer loyalty and brand trust. Brand trust also has a positive and significant effect on consumer loyalty and provides complementary partial mediation in the relationship between electronic word of mouth and consumer loyalty, with a VAF value of 61.36%. The indirect effect, which was greater than the direct effect, indicates that building brand trust is the primary mechanism through which online reviews are transformed into consumer loyalty. The findings imply that MSME sellers should manage authentic and credible customer reviews while maintaining consistency in product quality, service, delivery, and complaint handling to develop sustainable consumer loyalty.